Environmental defenders, indigenous peoples and organized violence in contemporary Latin America. The opportunity of Acuerdo de Escazú (Rivista di Studi e Ricerche sulla criminalità organizzata, 2022)
This paper considers the Escazú Agreement – the first arrangement dealing with the environment concluded by twelve Latin American countries – which has been in place for about one year. The agreement seeks to ensure environmental democracy while calling for environmentalists’ protection. The paper examines the regional context in which this agreement is implemented, which features extractivism, growing social and environmental conflict, violence against environmentalists, organized crime, and the fight of indigenous communities against extraction activities in their areas.
Keywords: Latin America, Escazú Agreement, environmentalists, indigenous people, violence, organized crime